Molecular characterization of extended-spectrum β-lactamases-producing Escherichia coli isolated from patients with bacteremia - Beatrice D. V. L. Souza; Guilherme Solveira; Guilherme F. R. de Souza; Henrique Orsi; Daiany R. P. De Lira; Iranildo do A. Fernandes; Adriano M. Ferreira; Alessandro L. Mondelli; Claudio T. Sacchi; Karoline R. Campos; Marlon B. N. Santos; Carlos H. Camargo; et al. (Brazilian Journal of Microbiology, 2026)
Bacteremia is a major health problem that affects millions of people worldwide. E. coli is one of the main pathogens associated with bacteremia and its resistance to the antimicrobial drugs, including β-lactams, has significantly increased in recent years. In view of the above, our objective was to determine the antimicrobial resistance profile of 60 E. coli isolates obtained from patients with bacteremia, as well as to characterize extended-spectrum β-lactamases (ESBL) -producing isolates. The highest resistance rates were observed for ciprofloxacin (33.3%), levofloxacin (31.7%), cefuroxime (20%) and cefotaxime (20%). Furthermore, 12 isolates (20%) were ESBL producers. Genomic analysis showed that 58.3% of these ESBL-producing isolates belonged to the phylogroup B2, ST131, serotype O25:H4 and carried the following ESBL-encoding genes: bla CTX−M−15 (66.7%), bla CTX−M−8 (16.7%), bla CTX−M−2 (8.7%) or bla CTX−M−27 (8.7%). Our data highlight the high frequency of E. coli ST131 among the ESBL-producing isolates obtained from patients with bacteremia in Botucatu, Brazil.